Practices of Freedom : Decentred Governance, Conflict and Democratic Participation - Griggs, Steven; Norval, Aletta J.; Wagenaar, Hendrik (Cambridge : Cambridge University Press, 2014)
The shift from government to governance has become a starting point for many studies of contemporary policy-making and democracy. Practices of Freedom takes a different approach, calling into question this dominant narrative and taking the variety, hybridity and dispersion of social and political practices as its focus of analysis. Bringing together leading scholars in democratic theory and critical policy studies, it draws upon new understandings of radical democracy, practice and interpretative analysis to emphasise the productive role of actors and political conflict in the formation and reproduction of contemporary forms of democratic governance. Integrating theoretical dialogues with detailed empirical studies, this book examines spaces for democratisation, institutional design, democratic criteria and learning, whilst mobilising the frameworks of agonistic and aversive democracy, informality and decentred legitimacy in cases from youth engagement to the Israeli-Palestinian conflict.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).
Keywords: Freedom; Democracy